Differentiation between malignant and benign musculoskeletal tumors using diffusion kurtosis imaging. - Ogawa, Masaki; Kan, Hirohito; Arai, Nobuyuki; Murai, Taro; Manabe, Yoshihiko; Sawada, Yusuke; Shibamoto, Yuta (Skeletal Radiology, 2019)
Objective: The purpose of this study was to evaluate differences in parameters of diffusion kurtosis imaging (DKI) and minimum apparent diffusion coefficient (ADCmin) between benign and malignant musculoskeletal tumors.Materials and Methods: In this prospective study, 43 patients were scanned using a DKI protocol on a 3-T MR scanner. Eligibility criteria were: non-fatty, non-cystic soft tissue or osteolytic tumors; > 2 cm; location in the retroperitoneum, pelvis, leg, or neck; and no prior treatment. They were clinically or histologically diagnosed as benign (n = 27) or malignant (n = 16). In the DKI protocol, diffusion-weighted imaging was performed using four b values (0-2000 s/mm2) and 21 diffusion directions. Mean kurtosis (MK) values were calculated on the MR console. A recently developed software application enabling reliable calculation was used for DKI analysis.Results: MK showed a strong correction with ADCmin (Spearman's rs = 0.95). Both MK and ADCmin values differed between benign and malignant tumors (p < 0.01). For benign and malignant tumors, the mean MK values (± SD) were 0.49 ± 0.17 and 1.14 ± 0.30, respectively, and ADCmin values were 1.54 ± 0.47 and 0.49 ± 0.17 × 10-3 mm2/s, respectively. At cutoffs of MK = 0.81 and ADCmin = 0.77 × 10-3 mm2/s, the specificity and sensitivity for diagnosis of malignant tumors were 96.3 and 93.8% for MK and 96.3 and 93.8% for ADCmin, respectively. The areas under the curve were 0.97 and 0.99 for MK and ADCmin, respectively (p = 0.31).Conclusions: MK and ADCmin showed high diagnostic accuracy and strong correlation, reflecting the accuracy of MK. However, no clear added value of DKI could be demonstrated in differentiating musculoskeletal tumors.